الملف النووي الايراني واثره على العلاقات الايرانية الامريكية (Comprehensive Journal of Science, 2026)
This study examines Iranian-American relations in the context of the Iranian nuclear issue, a central issue in international politics. It focuses on the impact of the Iranian nuclear program on the dynamics of bilateral relations between the two countries, with an emphasis on the growing tensions resulting from Iran's pursuit of nuclear energy. Since the Islamic Revolution in Iran in 1979, Iran has been a major source of American security concern in the Middle East, as the United States views Iran's nuclear ambitions as a threat to regional and international security.The study aims to analyze the impact of the nuclear agreement on improving or complicating relations between the two countries, in addition to examining the role of US sanctions in affecting the Iranian economy and domestic politics. It also sheds light on the positions of other major powers, such as Russia, China, and the European Union, which have had a significant influence in supporting or opposing US policy toward Iran. The study methodology is based on a descriptive and analytical approach, employing a historical approach to understand the evolution of Iranian-American relations over time. A comparative approach will also be applied to compare developments in relations between the two countries at different periods. The study tools include a literature review of previous research, a documentary analysis of official agreements, and reports from international organizations such as the United Nations and the International Atomic Energy Agency (IAEA).The study concludes that the Iranian nuclear program played a significant role in escalating political tensions between Iran and the United States, contributing to the widening of the differences between them. The results also show that US economic sanctions had a significant impact on the Iranian economy, giving the United States greater leverage in negotiations. The US withdrawal from the nuclear agreement also led to renewed tensions with Iran, which responded by violating its nuclear obligations.
Keywords: Iranian nuclear file - Iranian-American relations - Iranian nuclear agreement - nuclear weapons